Enhancing forage nutritional value in Persian clover (Trifolium resupinatum) and crimson clover (Trifolium incarnatum) through intercropping and optimized seeding rate - Mohammad Zamanian; Farid Golzardi; Harun Gitari; Emmanuely Nungula; Foroud Salehi; Saeid Heydarzadeh (Cogent Food & Agriculture)
The seeding rate holds the potential to enhance crop nutritional value; however, its impact on the forage quality of clover remains relatively unexplored. This study aimed to assess the impact of various cropping patterns and seeding rates on the forage yield and quality of Persian clover (Trifolium resupinatum L.) and crimson clover (T. incarnatum L.). A factorial experiment was conducted using a randomized complete block design with 10 treatments and three replications across two regions in Iran—Karaj and Shahrekord—over two cropping seasons (2020–2022). The experimental setup included five cropping patterns: Persian clover monoculture (PC100%), crimson clover monoculture (CC100%), and three replacement intercropping patterns: PC25%–CC75%, PC50%–CC50%, and PC75%–CC25%. Each pattern was evaluated at two seeding rates: 20 and 25 kg ha−1 (SR20 and SR25, respectively). The results indicated that the highest crude protein yield was observed in crimson clover monoculture at SR25 (1.03 Mg ha−1), followed by the PC25%–CC75% intercropping system at SR20 (1.00 Mg ha−1), both in Shahrekord during the second year. Additionally, the Persian clover monoculture at SR25 and the PC25%–CC75% intercropping system at SR20 in Karaj, as well as crimson clover monoculture at SR25 and the same intercropping system in Shahrekord, produced the highest crude protein yields. Furthermore, the PC50%–CC50% pattern at SR20 exhibited the highest forage quality for both species. Based on the findings, the PC25%–CC75% intercropping system with SR20 is recommended to farmers for enhancing forage productivity and quality in sustainable agricultural practices.